Green Initiatives Adoption: Perspective of E&E Manufacturing SMEs Sustainability - Yacob, Peter; Jaganathan, Mathivannan; Zakaria, Norria; Lee, Eng Keong; Nodeson, Suresh; Yee, Chew Fong; Fared, Mohamad (Serials Publications, 2017)
In recent years, the importance of the environmental agenda for the industry has been rising exponentially at the international level. Additionally, increasing consumers' awareness on the environmental impact of their consumption choices and their willingness to reduce their ecological footprint has created new market opportunities for manufacturers. Sustainable green practices have become the conscientious imperative expected from all manufacturing industries due to rising environmental awareness among today's society. Therefore, the objectives of this research were to determine the extent of green initiatives implementation in Electrical and Electronics (E&E) manufacturing SMEs as well as to examine the relationship between those practices and sustainable green practices. The quantitative data was obtained through a survey of 260 E&E manufacturing SMEs located throughout Malaysia. Analysis of the findings showed that there is an encouraging level of sustainable green practice implementation among the SMEs, with optimization of water conservation initiative as being the top priority and followed by energy efficiency. The result also revealed that waste management initiative not significantly affected sustainable green practices. The findings of this research provide new directions for future research and key implications concern the importance for firms and policymakers to work with sustainability issues using both internal and external perspectives.